2004
DOI: 10.1080/10640260490521415
|View full text |Cite
|
Sign up to set email alerts
|

Asian Body Image Satisfaction: Ethnic and Gender Differences across Chinese, Indo-Asian, and European-Descent Students

Abstract: This study extends previous research on ethnocultural differences in body image satisfaction by comparing two distinct Asian groups with a European descent group (N = 1471). Canadian undergraduates completed self-report body image measures. Participants descended from China reported the lowest levels of body satisfaction. Body satisfaction of participants descended from Indo-Asia was the next lowest, significantly lower than their European descent counterparts. The body satisfaction of women was lower than tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
53
1
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(64 citation statements)
references
References 30 publications
5
53
1
1
Order By: Relevance
“…Evidence of dissatisfaction with facial attractiveness has been reported for young adult Asian males in one study conducted in Canada by Kennedy et al (2004). In this study, male and female Chinese undergraduate students both reported lower satisfaction with facial attractiveness than with other parts of the body as measured by the body image subscale of the Derogatis Sexual Functioning Inventory (Derogatis, 1978).…”
Section: Body Features Associated With Body Dissatisfaction Across Cumentioning
confidence: 69%
“…Evidence of dissatisfaction with facial attractiveness has been reported for young adult Asian males in one study conducted in Canada by Kennedy et al (2004). In this study, male and female Chinese undergraduate students both reported lower satisfaction with facial attractiveness than with other parts of the body as measured by the body image subscale of the Derogatis Sexual Functioning Inventory (Derogatis, 1978).…”
Section: Body Features Associated With Body Dissatisfaction Across Cumentioning
confidence: 69%
“…Women are more prone to experiencing body dissatisfaction than men 6 . Researches have been conducted that suggest that the majority of women are dissatisfied with their body 6 . In this study, their body dissatisfaction had significant difference in relation to men's.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, however, the emphasis on fitness has become more prevalent among other societies as well as Western cultures 6,7,8,9,10 . Messages in Western media regarding attractive and ideal body types may be a cause of body dissatisfaction 11 .…”
Section: Introductionmentioning
confidence: 99%
“…(4,7) This is supported by the increasing number of reports on eating disorders occurring in Asia, a region where eating disorders were previously thought to be rare. (8) Although the prevalence rate of eating disorders in Asia is still lower than that in the West, (8,9) studies have found that Southeast Asian individuals exhibit lower levels of body satisfaction, (10) greater eating disorder psychopathology and greater concerns about their weight as compared to their Western counterparts. (11,12) Kok and Tian reported that Singaporean adolescents exhibited greater levels of body dissatisfaction and a higher drive for thinness as compared to American undergraduate students.…”
Section: Introductionmentioning
confidence: 99%